PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE LEARNING TOURNAMENT UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KELARUTAN DAN HASIL KALI KELARUTAN DI KELAS XI MAN 1 PEKANBARU - Wardhani, Eva Yuli Wardhani Yuli; Amran, Elva Yasmi; Erviyenni, Erviyenni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The Research about application of the active learning strategy type learning tournament has been done to improve student’s achievement on the topic of solubility and solubility product constant in class XI MAN 1 Pekanbaru. This research is experimental research based on pretest-posttest design. The samples of this research were the students of class Xl IPA 2 as the control class and students of class XI IPA 1 as the experimental class that randomly selected after testing homogeneity. Experimental class is a class that is applied active learning strategy type learning tournament, while the control class was not. Data analysis technique used is the t-test. Based on analysis of data obtained tarithmetic> ttable is 2,14 > 1,66, means that the application of active learning strategy type true false chain can improve student achievement on the subject of solubility and solubility product constant in class XI MAN 1 Pekanbaru where the effect of an increase is 6,77%.Key Words : Active Learning Strategy Type Learning Tournament, Learning Achievement, and Solubility and Solubility Product Constant